2003
DOI: 10.1080/15298860309025
|View full text |Cite
|
Sign up to set email alerts
|

“How European am I?”: Prejudice Expression and the Presentation of Social Identity

Abstract: We propose that the expression of prejudice may be used for publicly validating a social identity. This assumption was investigated in a Greek political context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 39 publications
2
21
0
3
Order By: Relevance
“…Baumeister, 1982;Schlenker, 1980). For instance, individuals consider the group membership of the audience before expressing prejudiced views or opinions (Crandall, Eshelman, & O'Brien, 2002;Klein, Licata, Azzi, & Durala, 2003). Furthermore, Tetlock (1981) showed that participants' public attributions for their actions seemed tailor-made to create favorable impressions in others.…”
Section: The Importance Of the Context Of Communicationmentioning
confidence: 99%
“…Baumeister, 1982;Schlenker, 1980). For instance, individuals consider the group membership of the audience before expressing prejudiced views or opinions (Crandall, Eshelman, & O'Brien, 2002;Klein, Licata, Azzi, & Durala, 2003). Furthermore, Tetlock (1981) showed that participants' public attributions for their actions seemed tailor-made to create favorable impressions in others.…”
Section: The Importance Of the Context Of Communicationmentioning
confidence: 99%
“…For instance, research on symbolic self-completion theory suggests that individuals use symbols and other socially-recognized indicators to communicate aspects of their desired personal identity or self-image to others (Braun & Wicklund, 1989;Gollwitzer & Kirchhof, 1998;Wicklund & Gollwitzer, 1981). Likewise, research suggests that individuals are more likely to display particular identity-relevant behaviors (e.g., prejudicial statements against an outgroup) when they are motivated to convey to others an impression of themselves as good ingroup members (Klein, Licata, Azzi, & Durala, 2003;Klein, Spears, & Reicher, 2007;Noel, Wann, & Branscombe, 1995). At the group level, we might therefore expect that-if symbols can indeed make groups seem more united and intimidating-group members would be more likely to create and display group identity symbols when they are motivated to convey that impression of their group to others (for instance, when they are in a competitive rather than cooperative context).…”
Section: What Motivates the Use Of Symbols?mentioning
confidence: 99%
“…Some of their norms are antagonistic to those of the EU-such as their friendly attitudes toward Serbia and Yugoslavia during the Kosovo war and the widespread prejudice toward the Turks (which is inconsistent with the norms of tolerance supposed to govern the EU). Klein, Licata, Azzi, and Durala (2003) conducted a study to understand how Greeks would adjust their expressed attitude toward the Turks, a potential source of conflict between the two allegiances, as a function of whether they addressed an audience of prototypical EU members or of Greeks. Klein et al hypothesized that participants' response to this situation would depend on their level of identification with Europe.…”
Section: Identity Consolidation In the Context Of A Double Identitymentioning
confidence: 99%